Effects of ethyl-esterization, chain-lengths, unsaturation degrees, and hyperthermia on carcinostatic effect of omega-hydroxylated fatty acids - Kusumoto, K.; Kageyama, K.; Matsuda, T.; Tomura, T.T.; Munakata, H.; Tanaka, H.; Yazama, F.; Miwa, N. (Experimental Oncology, 2007)
Aim: To evaluate promotive effect of hyperthermia on the carcinostatic activity of synthesized omega-hydroxy fatty acids (wHFAs) and their ethylesters agaist Ehrlich ascites tumor (EAT) cells. Methods: EAT cells were cultured with either wHFAs or their ethylester derivatives in a water bath at either 37 °C or 42 °C for 30 min, followed by incubation in a CO2 incubator for 20 or 72 h. Mitochondrial dehydrogenase-based WST-1 assay and trypan blue dye exclusion assay were then conducted after incubation. Morphological changes were observed by scanning electron microscopy (SEM). Results: Omega-HFA having a saturated 16-carbon straight-chain (wH16:0) was the most carcinostatic (at 37 °C – viability level: 60.0%; at 42 °C – 49.6% (WST-1)) among saturated and unsaturated wHFAs with 12, 15 or 16 carbon atoms, when administrated to EAT cells at 100 µM for 20 h. Carcinostatic activity was markedly enhanced by ethyl-esterization of saturated fatty acids, such as wH16:0 (at 37 °C – 42.3%; at 42 °C – 11.2% , ibid) and wH15:0 (at 37 °C – 74.6%; at 42 °C – 25.3% , ibid), and their unsaturated counterparts were extremely effective only in combination with hyperthermia. Prolongation of the incubation period to 72 h at the same concentration increased appreciably their carcinostatic effect (wH16:0 ethylesther: 1.3%; wH15:0 ethylesther: 8.0%). These values were also supported by dye exclusion assay. The carcinostatic activity enhanced more markedly by hyperthermia (1.2%; 2.1%, ibid). SEM shows that wH16:0 ethylester-exposed EAT cells underwent extensive injury, such as deformation of cell structure or disappearance of microvilli. Conclusions: wH16:0 ethylester possesses high carcinostatic activity in vitro in combination with hyperthermia and may be utilized as potent anticancer therapeutic agent. Цель: проанализировать усиливающий эффект гипертермии на канцеростатическую активность синтезированных омегагидроксилированных жирных кислот (HFAs) и их этиловых эфиров по отноению к клеткам асцитной опухоли рлиха (EAT). Методы: клетки EAT инкубировали с HFAs или их этилэфирными производными на водной ане при 37 ° или 42 ° в течение 30 мин с дальнейим культивированием в 2 инкубаторе на протяжении 20 или 72 ч, после чего анализировали жизнеспособность клеток методами анализа WST-1, основанного на активности митохондриальных дегидрогеназ, и по включению трипанового синего. Морфологические изменения клеток определяли с использованием сканирующей электронной микроскопии. Результаты: при культивации клеток EAT в присутствии 100 M соединений в течение 20 ч омега-HFA с насыщенной 16-углеродной прямой цепью (H16:0) проявляли наиболее выраженный канцеростатический эффект (при 37 ° уровень жизнеспосоности составил 60,0%; при 42 ° 49,6% (WST-1)) по сравнению с таковым насыщенных и ненасыщенных HFAs, содержащих 12, 15 или 16 атомов углерода. анцеростатическая активность значительно возрастала при этилэтерификации насыщенных жирных кислот, таких как H16:0 (при 37 ° 42,3%; при 42 ° 11,2%, ibid) и H15:0 (при 37 ° 74,6%; при 42 ° 25,3% , ibid), в то время как производные ненасыщенных кислот были высокоэффективны только в комбинации с гипертермией. Увеличение периода инкубации клеток до 72 ч при той же концентрации веществ приводило к значительному увеличению их канцеростатического действия (этиловый эфир H16:0 1,3%; этиловый эфир H15:0 ethylesther 8,0%), подтвержденного данными окраски трипановым синим. рименение гипертермии также усиливало канцеростатическое действие соединений (1,2%; 2,1%, ibid). Результаты исследования методом SEM показали, что клетки EAT, инкубированные с этиловым эфиром H16:0, разруаются с нарушением клеточной структуры и исчезновением микроволокон. Выводы: в комбинации с гипертермией этиловый эфир H16:0 про ет высокую канцеростатическую активность in vitro, что говорит о возможности применения соединения в терапии опухолевых заболеваний.